The queer case of video games: orgasms, Heteronormativity, and video game narrative. Issue 1 (1st January 2016) - Chess, Shira
ABSTRACT: In recent years, scholars have theorized about the narrative potential of video games. These conversations have helped to situate a complex new medium into the parameters of older forms of storytelling. This paper argues that these debates often privilege heteronormative formulations of narrative structure. Building on the work of Judith Roof (1996. Come as you are: Sexuality and narrative . New York: Columbia University Press), I illustrate how traditional narrative theory relies on masculine, heteronormative conceptualizations of a necessarily reproductive climax. Queer narrative theory, in contrast, focuses on the pleasurable possibilities embedded in the middle of the narrative. Similarly, gaming narratives play in the middle spaces where queer narrative thrives. Using this as a theoretical model, I explore how games are more effective in the narrative middle and provide a new lens for both narrative scholars and gaming scholars.